Millenials Lifestyle Phenomenon dan Store Atmosphere terhadap Buying Decision - Sulastri Fazriah; Nor Norisanti; Kokom Komariah (IPM2KPE, 2019)
The purpose of this study was to determine the effect of store lifestyle on purchasing decisions. The research method in this study uses the type of sample included in the random sampling sample and by distributing questionnaires as many as 100 to consumers. The analysis technique used is multiple linear analysis techniques, and for hypothesis testing is a statistical test using simultaneous (f test). Based on the results of the F test the probability value sig 0,000 <0.1. In conclusion, life style (X1) and Store Atmosphere (X2) have a significant effect on purchasing decisions (Y). Keywords: Purchasing Decisions, Lifestyle, Store Atmosphere